Effects of participation in a U.S. trial of newborn genomic sequencing on parents at risk for depression. Issue 1 (26th July 2021) - Schwartz, Talia S.; Christensen, Kurt D.; Uveges, Melissa K.; Waisbren, Susan E.; McGuire, Amy L.; Pereira, Stacey; Robinson, Jill O.; Beggs, Alan H.; Green, Robert C.; ,; Bachmann, Gloria A.; Rabson, Arnold B.; et al.
Abstract: Much emphasis has been placed on participant's psychological safety within genomic research studies; however, few studies have addressed parental psychological health effects associated with their child's participation in genomic studies, particularly when parents meet the threshold for clinical concern for depression. We aimed to determine if parents' depressive symptoms were associated with their child's participation in a randomized‐controlled trial of newborn exome sequencing. Parents completed the Edinburgh Postnatal Depression Scale (EPDS) at baseline, immediately post‐disclosure, and 3 months post‐disclosure. Mothers and fathers scoring at or above thresholds for clinical concern on the EPDS, 12 and 10, respectively, indicating possible Major Depressive Disorder with Peripartum Onset, were contacted by study staff for mental health screening. Parental concerns identified in follow‐up conversations were coded for themes. Forty‐five parents had EPDS scores above the clinical threshold at baseline, which decreased by an average of 2.9 points immediately post‐disclosure and another 1.1 points 3 months post‐disclosure (both p ≤ .014). For 28 parents, EPDS scores were below the threshold for clinical concern at baseline, increased by an average of 4.7 points into the elevated range immediately post‐disclosure, and decreased by 3.8 points at 3 months post‐disclosure (both p < .001). Nine parents scored above thresholds only at 3 months post‐disclosure after increasing an average of 5.7 points from immediately post‐disclosure ( p < .001). Of the 82 parents who scored above the threshold at any time point, 43 (52.4%) were reached and 30 (69.7%) of these 43 parents attributed their elevated scores to parenting stress, balancing work and family responsibilities, and/or child health concerns. Only three parents (7.0%) raised concerns about their participation in the trial, particularly their randomization to the control arm. Elevated scores on the EPDS were typically transient and parents attributed their symptomatology to life stressors in the postpartum period rather than participation in a trial of newborn exome sequencing.